The effect of fragmentation on phlebotomine communities (Diptera: Psychodidae) in areas of ombrophilous forest in São Luís, state of Maranhão, Brazil - Azevedo,PCB (2011)
The aim of this study was to determine whether an edge effect could be observed in the structure and composition of phlebotomine assemblages in five forest fragments on São Luís Island. The study also investigated whether there were any differences in species along the forest edge-to-interior gradient and in species richness and abundance between the fragments studied. To capture the insects a transect was defined in each fragment, and eight light traps were set up at 15 m intervals from the edge. Phlebotomines were found in all fragments, and a total of 2972 specimens (1188 males and 1784 females) belonging to 24 species were collected. Of these, the most abundant was Lutzomyia antunesi (Coutinho), followed by Brumptomyia avellari (Costa Lima), L. infraspinosa (Mangabeira), L. flaviscutellata (Mangabeira), L. claustrei Abonnenc, Léger & Fauran, L. wellcomei (Fraiha, Shaw & Lainson), L. sordellii (Shannon & Del Ponte) and L. paraensis (Costa Lima). No significant differences were observed in the number of individuals or species along the edge-to-interior gradient. However, a higher distribution of some species in certain regions of the forest could be observed graphically. There was no correlation between fragment size and the number of species or individuals.